APPLICATION OF THE ELGAMAL ALGORITHM TO WEB-BASED TEXT MESSAGE SECURITY - Ilham Rizki Ananda; Mhd Furqan; Rakhmat Kurniawan (Sean Institute, 2022)
The increasing use of information technology to support human work in various activities related to computers as a medium, so security and privacy issues are a very important aspect of information systems for data, messages and information. Encryption is the best way to protect information and device data. This research aims to produce a chat application using ElGamal Algorithm in text message security. The method used to encrypt the original text message that will be processed by the system so that the encrypted message results appear in the database not in the form of the original text or original message. Where the encryption process goes through many initial processes, namely the generation of keys represented by various numbers, then enter the encryption stage with the process using the public key for the encryption process. For the next stage, namely the decryption stage of the message encryption results so that it can be seen and read by the recipient. The results of this research are: Group Chat that is able to apply the Elgamal cryptographic algorithm in securing communication in the process of inputting messages to the database and displaying messages from the database to the application interface.